Effects of improved nutrition in pregnant reindeer on milk quality, calf birth weight, growth, and mortality - Rognmo, Arne; Markussen, Karl Annar; Jacobsen, Endre; Grav, Hans J.; Blix, Arnoldus Schytte (Rangifer, 1983)
A group of 35 pregnant reindeer (Rangifcr tarandus) was divided into two groups in mid-February. Until calving in May one of the groups (L) received lichen ad lib., while the other group (IN) received an improved diet, rich in protein and minerals. After calving both groups received the same improved diet. In both groups it was distinguished between young (<3 years) and old (>3 years) animals. At the start of the experiment the body weight of L-young animals was 58.5 ± 4.6 kg, IN-young 56.2 ± 2.8 kg, L-old 70.3 ± 6.0 kg and IN-old 68.2 ± 4.8 kg. At calving the weights of the same animals were 55.9 ± 4.5 kg (L-young), 68.1 ± 2.5 (IN-young), 70.0 ± 6.9 kg (L-old) and 81.6 ± 6.8 kg (IN-old). Birth weight of IN-young calves was 4.5 ± 0.7 kg and of L-young calves 3.7 ± 0.5 kg. Birth weight of IN-old calves was 5.7 ± 0.8 kg and of L-old calves 4.4 ± 0.6 kg. The birth weight of the calves in all groups was correlated to the weight of the female just prior to calving. Growth rates in all but the IN-old group were not different, the IN-old group showing a significantly higher growth rate than the other groups. In mid-September, however, the average body weight for the calves from the L and IN-groups did not differ significantly. Neither chemical composition nor total energy content of the milk differed significantly between the groups. Total mortality in the L-group was 28% as compared to 7% in the IN-group. Two females in the IN-old group had not given birth at the end of the experimental period.Virkningen av bedret ernæring til drektige reinsimler på melkekvalitet, kalvenes fødselsvekt, vekst og dødelighet.Abstract in Norwegian / Sammendrag: En flokk på 35 drektige reinsimler (Rangifer tarandus) ble delt i to grupper i midten av februar. Frem til kalving i mai ble den ene gruppen gitt lav ad lib. (L-gruppe), mens den andre gruppen ble tilleggsforet med 2 kg RF - 71/dag (IN-gruppe). Etter kalving ble begge gruppene gitt 2 kg RF - 71/dag. Innen begge gruppene ble det skilt mellom unge (<3 år) og gamle (>3 år) simler. Ved forsøkets start var kroppsvekten for unge simler ca. 57 kg, og for gamle simler ca. 69 kg, i begge ernæringsgruppene. Ved kalving var kroppsvekten for unge simler 55.9 ± 4.5 kg (L-gruppe), og 68.1 ± 2.5 kg (IN-gruppe) mens kroppsvekten for gamle simler var 70.0 ± 6.9 kg (L-gruppe) og 81.6 ± 6.8 kg (IN-gruppe). Fødselsvekt for kalver etter IN-unge simler var 4.5 ± 0.7 kg, og 3.7 ± 0.5 kg for kalver etter L-unge simler. De tilsvarende fødselsvektene for kalver etter gamle simler var 5.7 ± 0.8 kg (IN-gruppe) og 4.4 ± 0.6 kg (L-gruppe). Fødselsvektene var korrelert til simlenes kroppsvekt like før kalving. Kalveveksten i de første tre ukene etter fødselen var signifikant høyere for kalver etter IN-gamle simler, sammenlignet med kalveveksten i de øvrige tre gruppene, som ikke var innbyrdes signifikant forskjellige. I midten av september var det ingen signifikante forskjeller i kalvenes kroppsvekt gruppene imellom. Det var ingen signifikante forskjeller hverken i totalt energiinnhold eller i kjemisk sammensetning av melken fra simlene i de to ernæringsgruppene. Total dødelighet for kalver i L-gruppen var 28% mot 7% i IN-gruppen i løpet av de tre første ukene etter fødselen. To av de gamle simlene i IN-gruppen hadde ikke kalvet ved forsøkets slutt.Kantavien porovaatimien parannetun ravinnon vaikutus maidonlaatuun, vasojen syntymåpainoon, kasvuun ja kuolleisuuteen.Abstract in Finnish / Yhteenveto: 35 kantavan porovaatimen (Rangifer tarandus) lauma jaettiin kahteen ryhmaan helmikuun puolivålisså. Vasomiseen saakka toukokuussa annettiin toiselle ryhmalle jåkalaa ad. Ub. (L-ryhmå), kun taas toinen ryhma sai lisåravintona 2 kg RF-71 rehua påivåsså (IN-ryhmå). Vasomisen jålkeen annettiin molemmille ryhmille 2 kg RF-71 rehua påivåsså. Molemmissa ryhmisså erotettiin nuoret (< 3-vuotiaat) ja vanhat (> 3-vuotiaat) vaatimet toisistaan. Tutkimuksen alkuvaiheessa oli nuorten vaatimien ruumiinpaino n.57 kg, ja vanhojen vaatimien n.69 kg, molemmissa ravintoryhmisså. Vasomisen aikana oli nuorten vaatimien ruumiinpaino 55,9 ± 4,5 kg (L-ryhmå), ja 68,1 ± 2,5 kg (IN-ryhmå), kun taas vanhojen vaatimien ruumiinpaino oli 70,0 ± 6,9 kg (L-ryhmå) ja 81,6 ± 6,8 kg (IN-ryhmå). Vasojen syntymåpaino IN-nuorten vaatimien ryhmåsså oli 4,5 ± 0,7 kg, ja 3,7 ± 0,5 kg L-nuorten vaatimien ryhmåsså. Vastaavat syntymåpainot vanhojen vaatimien vasoilla olivat 5,7 ± 0,8 kg (IN-ryhmå) ja 4,4 ± 0,6 kg (L-ryhmå). Syntymåpainot olivat vastaavuussuhteessa vaatimien ruumiinpainoon våhåå ennen vasomista. IN-vanhojen vaatimien vasojen kasvu ensimmåisten kolmen viikon aikana syntymån jålkeen oli merkittåvåsti korkeampi, verrattuna niiden kolmen muun ryhmån vasankasvuun, jotka eivåt olleet keskenåån merkittåvån erilaisia. Vasojen ruumiinpainossa ryhmien kesken ei ollut mitåån merkittåviå eroavaisuuksia syyskuun puolivålisså. Nåiden kahden ravintoryhmån vaatimien maidossa ei ollut mitåån merkittåviå eroja kokonaisuudessa ravinnon sisåltoon eikå kemialliseen kokoonpanoon nåhden. Vasojen kokonaiskuolleisuus L-ryhmåsså oli 28% ja IN-ryhmåsså 7% kolmena ensimmåisenå viikkona syntymån jålkeen. Kaksi vanhaa vaadinta IN-ryhmåsså ei ollut vasonut tutkimuksen lopussa.